Спіральна комп’ютерна томографія шиї з різними варіантами техніки сканування у діагностиці нейропатичних стенозів гортані у пацієнтів із раком щитоподібної залози - Паламарчук, В. О.; Черноусов, Я. І. (Clinical Endocrinology and Endocrine Surgery, 2014)
The aim of the study was to improve the efficiency of diagnostics and treatment of patients with thyroid cancer (TC) including invasive forms accompanied by neuropathic stenosis of the larynx and trachea through the adoption of multislice computed tomography (MSCT) with different scanning technique. From 2011 to 2012 72 patients with confirmed thyroid cancer underwent preoperative laryn-geal examination by MSCT. Method of motility disorders of the larynx with vocal elements breakdown studing has diagnostic efficiency of 100%. MSCT in patients with thyroid cancer with carrying out vocal probes can effectively identify violations of medialization of the vocal cords and with breath inspiratory – asymmetry of aryepiglottic folds. MSCT without vocal maneuvers does not provide sufficient diagnostic information about the functional state of the vocal apparatus of the larynx. Three-dimensional reconstruction and virtual laringotraheobronchoscopy can be used as an additional criterion when planning surgical treatment in patients with malignant neoplasms of thyroid complicated with neuropathic laryngeal and tracheal compression.